Angle stable locking nails versus conventionally locked intramedullary nails in proximal tibial shaft fractures: A biomechanical study - Thelen, Simon; Betsch, Marcel; Grassmann, Jan-Peter; Spoor, Vera; Eichler, Christian; Koebke, Juergen; Windolf, Joachim; Hakimi, Mohssen; Wild, Michael (Archives of Orthopaedic and Trauma Surgery, 2012)
Introduction A tibial nail with fixed-angle locking screws intends to combine the advantages of angular stability and intramedullary stabilization in extraarticular proximal tibial fractures. The goal of this study is to analyze if the angle stable tibial nail (ASN) is biomechanically more stable than an established conventional standard nail (CN). Methods Two types of nails were compared on a series of ten matched pairs of human tibiae. After setting a proximal tibial defect fracture, the intramedullary stabilized tibiae were axially loaded starting from 100 N increasing in steps of 100 N after every 200 cycles until failure was reached. Failure was defined as deformation of the fracture gap, fracturing of the bone or the implant. Results The two types of nails showed no significant difference in terms of maximum tolerated load, maximum cycles repeated or axial deformation of the bone-implant construct. The mean load at failure was 1,365 N for the CN and 1,195 N for the ASN. The mean axial deformation for conventional (19 mm) and angle stable nail (21 mm) did not differ significantly. Slightly less nail or screw loosening was noticed with the fixed-angle nail. Conclusion No significant difference in stability between the two compared implants could be demonstrated. A trend could be shown indicating that the rate of nail loosening in the proximal osteotomized part of the bone was lower for the angle stable nail. This trend, however, could not be substantiated statistically. © Springer-Verlag 2011.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Angle stable intramedullary nail; Biomechanical testing; Extraarticular proximal tibial fractures; Fixed-angle nail